Olympic Mountain pursuit - Bailey, Jodie (Pacific Northwest K-9 Unit., 2023)
"Four years ago, former US Marshal Jackson Dean left his job after falling for a witness--who's suddenly the target of an assassin. Now it's up to Jackson and his K-9 partner to protect single mom Everly Lopez and her young daughter when Everly's identity is blown. But with hired killers looking for a payday, Jackson must use all his resources to stop them from silencing Everly permanently."--Page 4 of cover.